Kontribusi Performance Assessment Dalam Meningkatkan Kemandirian Siswa - Maghhfirah, Naily; Farikhin, Fikri (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2023)
The educational environment has an important role in children's independence. Schools or other educational institutions are expected to be able to foster, grow, and develop the independence of their students. Miftahul Ulum Kindergarten, Sucolor, Maesan, Bondowoso is one of the educational institutions that is aware of the importance of developing children's independence and participates in taking attitudes in shaping the character of their students, especially in terms of independence. Miftahul Ulum Kindergarten applies a performance assessment to each student in the Dhuha prayer activity which aims to make students independent in doing the Duha prayer. This study aims at describing how the implementation of performance assessment in Miftahul Ulum Kindergarten and how performance assessment contributes to the independence of early childhood, especially students of Miftahul Ulum Kindergarten. The research method applied is descriptive qualitative. The results showed that by implementing a performance assessment that was carried out regularly once a week, students who previously could only do the Duha prayer by reading the prayer readings aloud together as well as their movements, are now slowly able to do the Duha prayer regularly. individual. For those who have not been able to practice the Duha prayer, they easily know what things they need to practice and learn again so that they can immediately perform the Duha prayer independently through the performance assessment instrument